Business modeling under adversity : Resilience in international firms - Galkina, Tamara; Atkova, Irina; Gabrielsson, Peter (John Wiley & Sons, 2023)
Research Summary This study employs resilience theory and examines the dynamics of business modeling in international firms that enable them to resist environmental shocks under the adverse conditions of a global pandemic. Our multiple-case study shows that firms develop various dynamic states of their business models (BMs) during the resilience process; each state differs in terms of the scope of BM change and the concurrent degree of BM innovativeness. Shifts in dynamic states result from attaining certain resilience capabilities. We contribute to the dynamic view on BMs, and the process perspective on organizational resilience; we also advance BM research in the context of internationalization. Managerial Summary Under conditions of extreme disruptions that take the form of long-lasting adversity, international firms need to continuously adjust their BMs to brave force majeure and remain resilient. This study takes a dynamic perspective on business modeling and examines how international firms develop different dynamic states of their BMs to stay resilient under extreme uncertainty; each state differs in terms of the scope of BM change, concurrent degree of BM innovativeness and the attained resilience capabilities. We show that business modeling is a continuous task of international firms that allows them not only to resist adversity but also to open new markets.
Keywords: adversity; case study; internationalization; resilience; business models; fi=Kansainvälinen liiketoiminta|en=International Business|